Cyclosporin: Similimum for AIDS? - Finnegan, M.J.B. (British Homeopathic Journal, 1988)
The therapeutic vacuum in the wake of the AIDS epidemic invites speculation and the utilization of likely existing therapeutic agents in the treatment of HIV infected patients. Immunosuppressive agents, by virtue of their therapeutic action, produce toxic symptoms which have similarities to AIDS. Cyclosporin A (CyA) has a selective action on the T series of lymphocytes and is considered below.